VD_FINDINFO Décision / 2013 / 507 vom 15. März 2013 - VD Tribunal cantonal (2013)
DÉFENSE D'OFFICE, HONORAIRES, INDEMNITÉEN GÉNÉRAL | 135 al. 3 let. a CPP (CH), 393 al. 1 let. b CPP (CH), 395 let. b CPP (CH)